Preparing Future’s Community Empowerment: A Quantitative Study of The Correlation Between Empowerment And Human Resources In Ranu Pani And Sanan Tourism Village - Menur Kusumaningtyas; Irham Zaki; Sri Herianingrum; Muhammad Nafik Hadi Ryandono (Universitas Muhammadiyah Sidoarjo, 2022)
Human resources are the main support system for managing tourist villages. The main support system should be managed well. Managing human resources can reflected by empowering them to develop new skills based on their need to elaborate on the region’s potency. The region potency consists of culture, tourism place, and heritage. The aim of the research is to know about the correlation between empowerment and human resources in Ranu Pani Tourist Village and Sanan Tourist Village. This study used quantitative research. The data was collected using questionnaire. Data analysis was performed using descriptive, quantitative data. The result of this research is that the test distribution is normal by 0.871. The data were normal with a significance level of 0.55. The distribution number was greater than or greater than the significance number. The second was about ANOVA test. Based on ANOVA, the result was F= 56.245. This mean that there was a significant correlation between empowerment and human resources. Empowerment does influence human resources and human resources may influence empowerment. Even though there is significant correlation between empowerment and human resources, empowerment is still important for people particularly around village tourists. Society will be change quickly, and they need readiness to face the fast changing. Fast changing and society reflecting where does they live. Empowerment includes developing skills, abilities, knowledge and competency that need to be advanced around tourist villages. Human resources are the success or failure of tourist.